Albert O. Hirschman : an intellectual biography - Alacevich, Michele (Columbia University Press, 2021)
"Albert O. Hirschman was not, by any standard, a typical scholar. German by birth, by age thirty he had fought in two world wars, lived in seven different countries on three continents. He spoke and wrote in five languages, used multiple pseudonyms, and could pass as a French native. He held positions at a dozen elite institutions without ever having himself earned an advanced degree. Observed superficially, his scholarly output appears to be a patchwork of topics and methodologies, yet he was to no doubt one of the most important and influential social scientists of the Twentieth Century. In Albert O. Hirschman: An Intellectual Biography, economic historian Michele Alacevich makes sense of Hirschman's unrivaled intellectual output. To Hirschman's work he brings Hirschman's skepticism. His motto was the "it ain't necessarily so." To do so, he puts Hirschman's major work in context and with an eye towards the continuous dialog that Hirschman conducted with his intellectual and political counterparts and the debates of his time. As a result the book will consider Hirschman's contributions to the postwar reconstruction of Europe, development economics in Latin America specifically and the field more generally, organizational reform, the history and theory of market society, and the institutions of democracy. The book will conclude with reflections on Hirschman's legacy"--